Immunomodulatory Study of Different Solvent Extract of Elephantopus scaber Linn - Hiradeve, Sachin M.; Rangari, Vinod D. (Drug Research, 2017)
The aim and objective of present study is that to provide a scientific evidence for the immunomodulatory potential of Elephantopus scaber in vivo. The immunomodulatory activity was performed in petroleum ether, solvent ether, methanol and aqueous extract of aerial part and root of E. scaber by using models such as delayed type hypersensitivity, humoral antibody response to SRBC and carbon clearance test for phagocytic activity in Wistar rat. The observation and results of present study suggested that among the total 8 extract, only the petroleum ether and solvent ether aerial part extract of E. scaber significantly decreased in delayed type hypersensitivity (DTH), humoral antibody (HA) titre and phagocytic index thereby indicating significant immunosuppressant activity in experimental animals.
Keywords: Elephantopus scaber; Immunomodulators; DTH; phagocytic index